Enhancing light scattering effect of white LEDs with ZnO nanostructures - My Hanh Nguyen Thi; Nguyen Thi Phuong Loan; Hoang Van Ngoc (Institute of Advanced Engineering and Science, 2021)
Pc-LEDs, the lighting method that blends blue LED light with yellow light from phosphor to discharge white radiation, is one of the most advance known for high lumen output. However, pc-LEDs has inferior due to angular CCT deviation, which prevent pc-LEDs from reaching better performance. As a result, this research is conducted to address the need of pc-LEDs development by introducing a configuration doped with ZnO nanoparticles. The finite-difference time-domain (FDTD) method and the phosphor layer containing ZnO were applied in the experiments. The effect of ZnO-filled on the performance of color quality pc-LEDs is confirmed through calculated results. In particular, the uniformity of scattered light is improved with the presence of ZnO. In addition, ZnO particles also minimize the deviation of color temperature and enhance the color quality. Although there is a small decline in lumen output to achieve better color temperature uniformity, however, with suitable concentrations such as 0.25% N-ZnO, 0.25% S-ZnO, and 0. 75% R-ZnO, the decline is acceptable. The research on ZnO pc-LEDs demonstrates that this affordable and simple configuration can improve lighting properties and create other directions to enhance white light